Simulating the Weekly Cycle of NOx‐VOC‐HOx‐O3 Photochemical System in the South Coast of California During CalNex‐2010 Campaign. Issue 6 (20th March 2019) - Cai, Chenxia; Avise, Jeremy; Kaduwela, Ajith; DaMassa, John; Warneke, Carsten; Gilman, Jessica B.; Kuster, William; de Gouw, Joost; Volkamer, Rainer; Stevens, Philip; Lefer, Barry; Holloway, John S.; et al.
Abstract: United States Environmental Protection Agency guidance on the use of photochemical models for assessing the efficacy of an emissions control strategy for ozone requires that modeling be used in a relative sense. Consequently, testing a modeling system's ability to predict changes in ozone resulting from emission changes is critical. We evaluate model simulations for precursor species (NO x, CO, and volatile organic compounds [VOCs]), radicals (OH and HO2 ), a secondary pollutant (O3 ), and the model response of these compounds to weekend/weekday emission changes during California Nexus study in 2010. The modeling system correctly simulated the broad spatial and temporal variation of NO x and O3 in California South Coast. Although the model generally underpredicted the daytime mixing ratios of NO2 at the surface and overpredicted the NO2 column, the simulated weekend to weekday ratios are consistent with each other and match the observed ratios well. The modeling system exhibited reasonable performance in simulating the VOC compounds with fossil fuel origins but has larger bias in simulating certain species associated with noncombustion sources. The modeling system successfully captured the weekend changes of the enhancement ratios for various VOC species to CO and the relative changes of HO x, which are indicators of faster chemical processing on weekends. This work demonstrates satisfactory model performances for O3 and most relevant chemical compounds with more robust performance in simulating weekend versus weekday changes. Improved planetary boundary layer height simulations, a better understanding of OH‐HO2 cycling, continued improvement of emissions, especially urban biogenic emissions and emissions of oxygenated VOCs, are important for future model improvement. Key Points: We evaluate model simulations for O3, NO x, VOCs, and HO x as well as their response to weekend emission changes during CalNex 2010 The model results show a robust ability to simulate the weekend effect, for a majority of the relevant chemical species Further understanding is needed for urban biogenic emissions and emissions of oxygenated VOCs such as ethanol, methanol, and acetone